Re-considering internationalisation from the periphery: Introduction to the two linked articles. Issue 3 (1st December 2022) - Alemu, Sintayehu Kassaye; Qu, Mei; Sakhiyya, Zulfa; Trifuljesko, Sonja; Choi, On Hee
Abstract : While there is little agreement about the definitions, theories and practices of internationalisation, they have one thing in common. They tend to originate from Europe and North America and primarily serve the interests of Anglo-American academia (Ivancheva and Syndicus 2019; Marginson 2016; Rhoades et al. 2019). These two articles take a different perspective. They look at internationalisation from two kinds of peripheries and consider the strategies that peripheralised countries and people are using to try and create a more balanced or equal relationship between local or national interests and those of universities in Europe and North America. The first article considers internationalisation from peripheral countries in sub-Saharan Africa, China and Indonesia and explores the strategies of regional cooperation, 'balanced internationalisation' and marketisation (respectively) that they are adopting to resist marginalisation and dependency. The second article is written from the perspective of international students who are peripheralised within their host university and country in Europe. It explores the dilemmas students encounter when trying to negotiate language politics and the use of social media in order to participate more fully in the university and society.